2021
DOI: 10.1016/j.healun.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and wound repair during COVID-19

Abstract: While COVID-19 is best known as a respiratory infection, SARS-CoV-2 causes systemic disease manifestations including coagulopathies. Both dysregulated extracellular matrix remodeling pathways and circulating coagulation proteins are hallmarks of severe COVID-19 and often continue after the resolution of acute infection. Coagulation proteins have proven effective as biomarkers for severe disease and anti-coagulants are a mainstay of COVID-19 therapeutics in hospitalized patients. While much knowledge has been g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 66 publications
(75 reference statements)
0
3
0
4
Order By: Relevance
“…The increased risk of DU in individuals infected with COVID‐19 may be attributed to DU occurring in typical anatomical regions due to limited mobility and prolonged exposure to the same position during treatment. Simultaneously, alterations in the body's immune metabolism can impact wound healing progress, as well as abnormal inflammatory and coagulation responses following infection 23,24 . Additionally, it is noteworthy that COVID‐19, being a global pandemic, could potentially exert a greater strain on healthcare systems within ageing countries and those with low SDI, leading to an escalation in the burden of chronic diseases; however, there is currently insufficient updated data available to substantiate this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of DU in individuals infected with COVID‐19 may be attributed to DU occurring in typical anatomical regions due to limited mobility and prolonged exposure to the same position during treatment. Simultaneously, alterations in the body's immune metabolism can impact wound healing progress, as well as abnormal inflammatory and coagulation responses following infection 23,24 . Additionally, it is noteworthy that COVID‐19, being a global pandemic, could potentially exert a greater strain on healthcare systems within ageing countries and those with low SDI, leading to an escalation in the burden of chronic diseases; however, there is currently insufficient updated data available to substantiate this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…ACE/ACE2 balance disruption and activation of the rennin-angiotensin-aldosterone system caused by SARS-CoV-2 lead to disease progression, especially in patients with comorbidities, such as DM and cardiovascular diseases. [18] , [19] The binding of SARS-CoV-2 to ACE2 increases levels of angiotensin II (Ang II), a potent vasoconstrictor and pro-inflammatory molecule which exerts oxidative stress, mitochondrial dysfunction, endothelial cell damage, hypercoagulation and thrombosis (via free radical generation), and jeopardise proper neovascularisation for wound healing. 2 High levels of serum plasminogen activator inhibitor-1 (PAI-1) and D-dimers are consistent with microthrombi observed in COVID-19 patient autopsies.…”
Section: Discussionmentioning
confidence: 99%
“… 2 High levels of serum plasminogen activator inhibitor-1 (PAI-1) and D-dimers are consistent with microthrombi observed in COVID-19 patient autopsies. 19 Clinically, Inouye et al 2 reported free flap failure in patients with SARS-CoV-2, and Talmor et al . 20 described pedicled nasoseptal flap necrosis and failure due to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…O vírus foi descrito inicialmente em um paciente com pneumonia desconhecida, na cidade de Wuhan, na província de Hubei, China, em dezembro de 2019 (DOBESH; TRUJILLO, 2020;IBA et al, 2020a;LAZZARONI et al, 2021;MENACHERY;GRALINSKI et al, 2021).…”
Section: Introductionunclassified
“…As manifestações clínicas produzidas pelo SARS-CoV-2 são variadas, desde quadros assintomáticos e leves, a quadros mais graves, os quais podem evoluir para a síndrome do desconforto respiratório agudo (SDRA) e/ou falência múltiplas dos órgãos (HADID et al 2021;MENACHERY;GRALINSKI et al, 2021).…”
Section: Introductionunclassified